Peningkatan Pengelolaan Pendidikan Anak Usia Dini Melalui Implementasi Manajemen Pendidikan - Faridatul Jannah; Nur Hotimah; Desi Endang Maisuri; Dewi Apriana (Al Tahdzib: Jurnal Pendidikan Islam Anak Usia Dini, 2024)
The aim of this research is to elucidate the improvement of Early Childhood Education management at Attoriq Pamekasan through the implementation of educational management. The research method employed is qualitative descriptive, using interviews, observation, and documentation as data-gathering techniques. Data processing involves data reduction, data presentation, and conclusion drawing. The research findings illustrate that Attoriq PAUD School has a planning process involving full participation from the headmaster, teachers, and students to achieve clear goals and address existing problems. The organization is conducted considering management principles such as workforce grouping, authority determination, and time discipline. Each school member has their own responsibilities in line with the school's vision and mission. Implementation of educational activities aims to maintain discipline, adhere to instructions, and prioritize collective interests. The headmaster provides guidance and bonuses as appreciation for hard work and cooperation. Regular supervision is conducted to ensure all activities are in accordance with the plan and to identify and address weaknesses for continuous improvement of education quality.